Deep Culture and Political Shifts: Applying Causal Layered Analysis to Understand Pakistan’s Post-2013 Authoritarian Turn - Adil Khan; Ahsan ur Rahim; Haider Nisar Swati (ASIAN Journal of International Peace & Security (AJIPS), 2024)
This paper addresses Pakistan’s drift to authoritarianism after the 2013 General Elections using Causal Layered Analysis (CLA) as lens to deconstruct the various layers of political system. It looks at events, trends, institutions, policy, rhetoric/discourse, and myth/metaphor to give a conceptual analysis of why this transition has finally occurred and what cultural formations underpin it. The first level, the litany layer, analyzes how people and the media evaluated the changes in the political landscape. The second level, the systemic cause layer, discusses civil-military relations, judicial involvement, elections, economic issues, and changes in laws and policies. Security, nationalism, and governance within political discourses and how media and culture continue to either reinforce or subvert such authoritarian discourses are scrutinized in the discourse/worldview layer. The myth/metaphor layer examines archetypal cultural narratives, which shape people’s actions in politics and their receptiveness to authoritarianism. This way, numerous and interwoven strands, including civilizational variables and political transitions, come to the fore.